The Importance of Sharia Economy in Religious Moderation - Rusli Siri; Rahmi Rahmi (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
Research is motivated by the emergence of economic actors when conducting transactions without paying attention to the principle of justice as religious believers. Thus arose the division of the religious ummah. In fact, in the Islamic economy, one of the attitudes that need to be developed in transactions is mutual respect or not discriminating between Muslims and non-Muslims. The author tries to conceptualize the importance of the sharia economy in religious moderation. Islamic economic principles, such as justice, Amanah, and mutual respect will be developed in peace. The problem raised in this study is how the basic concept of Islamic economics in building the lives of Muslims and non-Muslims. As well as the importance of the Islamic economy in religious moderation. Whether the Islamic economy is at odds with the application of religious moderation. The research method used in this scientific work is descriptive qualitative. The author tries to explain the importance of the Islamic economy in religious moderation. The approach used is phenomenology. Where the author himself experiences and feels how important the Islamic economy is in the concept of religious moderation. A number of results obtained by the author include how important the Islamic economy is in religious moderation. To create peace and tranquility respecting each other's fellow religious believers must be the basic foundation in everyday life. In carrying out economic activities, sharia concepts will not be complete without being accompanied by religious moderation. Both Muslims and non-Muslims must be aligned in carrying out economic activities. This is in line with the basic principles of Islamic religious teachings and the sunnah of the Prophet Muhammad SAW. The time of the great prophet Muhammad SAW also practiced mutual respect in trading. Prophet Muhammad SAW never forbade carrying out economic activities with non-Muslims. It signifies that Islam justifies religious moderation in the economy